PEMBERDAYAAN MASYARAKAT PENGUSAHA MINYAK KELAPA MELALUI PEMBENTUKAN KELOMPOK USAHA BERSAMA (KUBe) DI DESA GELORA KECAMATAN SIKUR KABUPATEN LOMBOK TIMUR - Enggal Permana, Wahyu; Aulia Putri, Rizka; Wulandari, Retno; Aulia Putri, Yuni; Santiani; Hudaeri; Ghina Sabrina, Haura; Rienendra Sari, Desni; Rizki, Kurnia; Taufikurahman; Sulaimiah (Jurnal Wicara, 2025)
Empowerment of the coconut oil entrepreneur community in Gelora Village, Sikur District, East Lombok Regency through the establishment of a Joint Business Group (KUBe) called GEMARA (Gelora Maju Bersama). Gelora Village has great economic potential, but the community still faces challenges in marketing and business legality. The purpose of this activity is to improve the welfare of the community through the establishment of KUBe and the creation of Business Identification Numbers (NIB) for coconut oil entrepreneurs. The methods used in this activity include surveys, interviews, and data collection of business actors. This activity aims to identify the problems faced by coconut oil entrepreneurs and provide solutions through the establishment of KUBe, NIB, and halal certification. The establishment of KUBe is expected to increase access to capital, marketing, skills, and socio-economic networks for its members. In addition, business legality and halal certification will help coconut oil entrepreneurs expand the market and improve product quality. The results of this activity show that the formation of KUBe has succeeded in answering existing issues and is expected to improve community welfare and maximize the potential of the local economy in Gelora Village. KUBe members have the right to participate in the management and earn profits, as well as the obligation to comply with the rules and be active in group activities. With the potential of abundant natural resources, KUBe is expected to empower the community and create sustainable economic opportunities.